Location and Industrial Efficiency with Free Entry: A Reply - Gee, J. M. A. (Quarterly Journal of Economics, 1979)
I. Price behavior, 451.—II. Profit, price behavior, and cost efficiency, 452.—III. Mobility and long-run equilibrium, 453.—Conclusion, 454.